Web 2.0 services for collaborative spatial decision making. (2013) - Argiolas, Michele; Dessì, Nicoletta; Garau, Gianfranco; Pes, Barbara
Spatial information is a powerful way to integrate data and knowledge in intuitive maps, enabling spatial patterns and relationships to be instantly visible. This paper describes a Spatial Decision Support System (SDSS) that supports web-based data exploration in spatial decisional processes. Based on a cloud environment, the SDSS is made up of specialised modules providing well-defined services. Mash-ups integrate data from different resources on the internet and provide the user with a flexible and easy-of-use interface. The paper focuses on Web 2.0 technology as a way for sharing geospatial data under the umbrella of collaborative decision making and it aims to make both a conceptual and a practical contribution. Conceptually, it leverages on web-based data integration as a power technology to increase broadly and self-adaptive management of data with high user involvement. Practically, it illustrates how this technology can be effectively deployed in a real estate decision-making scenario.